Planar Finger-Shaped Antenna used in Ultra-Wideband Wireless Systems - Rashid Ali Fayadh; Mohd Fareq A. Malek; Hilal A. Fadhil; Fwen Hoon Wee (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Recently, extensive requirements have developed for ultra-wideband (UWB) technology that provides high activity and small size for use in small communication systems, remote sensing, and radar applications. Thus, we concentrated with high-resolution radar UWB antenna to cover Federal Communication Commission’s (FCC) standard UWB range (3.1-10.6 GHz). The proposed ideal-size and low-cost finger-shaped patch antenna of 24 mm x 19 mm printed on 40 mm x 35 mm rectangular Taconic TLY-5 material was designed and established through experiments and simulations. Results show that the two cut notches of 1.5 mm x 2 mm at the bottom corners of the patch can increase the bandwidth. To increase the radiation area and achieve more resonance frequencies, two cut slots at the top edge of the patch were designed in depth of 10 mm. Four parameters were considered in the analysis of the proposed antenna design, namely the feeder width, number of slots, number of notches, and feed gap space. The simulated and measured results of the main antenna parameters make the design suitable in applications of UWB wireless systems.